The significant impact of hot isostatic pressing on the corrosion behavior of Ti-6Al-4V alloy prepared by electron beam powder bed fusion - Hongyu Zheng; Yun Bai; Wentao Hou; Zirong Zhai; Lai-Chang Zhang; Shujun Li; Rui Yang (npj Materials Degradation)
Abstract This work investigated the effect of hot isostatic pressing (HIP) on the corrosion behavior of Ti-6Al-4V samples prepared by electron beam powder bed fusion (EB-PBF). After the HIP treatment, the TiO2 content decreased but the growth rate of passivation films increased, leading to increase in internal defect density, thereby degrading the corrosion resistance. Amongst the different factors impacted by HIP including pore defects, β-phase, texture and morphology of α-phase, the morphology of α-phase played a dominant role in determining the corrosion performance of EB-PBF processed alloy.